2017
DOI: 10.1001/jamapediatrics.2016.2332
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Disparities in Childhood Obesity Risk: Association With an Oxytocin Receptor Polymorphism

Abstract: IMPORTANCE Pediatricians are paying increased attention to the effects of socioeconomic status (SES) on children's health. Low SES is a robust predictor of obesity across the life course and may interact with genes affecting metabolism to influence obesity risk. Recent animal literature and burgeoning human research suggest that the hormone oxytocin (OT) may be important for metabolic regulation. To date, this association has not been examined in children.OBJECTIVES To examine whether an OT receptor polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 43 publications
0
28
0
Order By: Relevance
“…In these patients, fairly low levels of oxytocin have been reported in the CSF 99 , and post-mortem studies have identified a reduced number of oxytocin-expressing neurons in the PVN of the hypothalamus 100 . In addition, polymorphisms of the oxytocin receptor (A-allele of rs53576) are associated with increased risk of obesity in children of low socioeconomic status 101 .…”
Section: Body Weightmentioning
confidence: 99%
“…In these patients, fairly low levels of oxytocin have been reported in the CSF 99 , and post-mortem studies have identified a reduced number of oxytocin-expressing neurons in the PVN of the hypothalamus 100 . In addition, polymorphisms of the oxytocin receptor (A-allele of rs53576) are associated with increased risk of obesity in children of low socioeconomic status 101 .…”
Section: Body Weightmentioning
confidence: 99%
“…It has been speculated that the relatively elevated cholesterol levels in obesity may boost highaffinity binding of oxytocin to the OXTR [27,141]. Support for the assumption that oxytocin signaling is altered in obesity comes from studies linking the OXTR gene to body weight [142,143] and the observation that overweight subjects as well as newly diagnosed diabetic patients display lower circulating concentrations of oxytocin when compared to normalweight controls [144]. Patients with Prader-Willi syndrome, who suffer from hyperphagic obesity as a consequence of persistent food craving, display a 40% reduction in the number and size of oxytocin neurons [145].…”
Section: Oxytocin As a Potential Intervention In Eating Disorders Andmentioning
confidence: 99%
“…When raised in high SES environments, lower BMIs were observed. The obesity risk for children with the GG genotype was not influenced by SES [29]. Similarly, the National Health Interview Survey (1997—2005) found that foreign born men and women from Africa have a lower likelihood of obesity than African American’s born in the USA [30].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the National Health Interview Survey (1997—2005) found that foreign born men and women from Africa have a lower likelihood of obesity than African American’s born in the USA [30]. It is evident that health outcomes can be affected by certain genetic predispositions, but there is also an interplay between genetics and environmental factors [29]. …”
Section: Introductionmentioning
confidence: 99%